Deciphering the roles of tobacco MYB transcription factors in environmental stress tolerance - Li, Xiaoxu; Guo, Cun; Li, Zhiyuan; Wang, Guoping; Yang, Jiashuo; Chen, Long; Hu, Zhengrong; Sun, Jinghao; Gao, Junping; Yang, Aiguo; Pu, Wenxuan; Wen, Liuying (Frontiers in Plant Science, 2022)
The MYB members play important roles in development, metabolism and various stress tolerance in plant. In the current study, a total of 246 tobacco R2R3-MYB transcription factors were identified and systemically analyzed from the latest genome annotation. The newly identified tobacco members were divided into 33 subgroups together with the Arabidopsis members. Furthermore, 44 NtMYB gene pairs were identified to arise from duplication events, which might lead to the expansion of tobacco MYB members. The expression patterns were revealed by transcriptomic analysis. Notably, the results from phylogenetic analysis, synthetic analysis, and expression analysis were integrated to predict potential functions of these members. Particularly, NtMYB102 was found to act as the homolog of AtMYB70 and significantly induced by drought and salt treatments. The further assays revealed that NtMYB102 had the transcriptional activities, and overexpression of the encoding gene enhanced the drought and salt stress tolerance in transgenic tobacco. The results of this study may be relevant for future functional analyses of the MYB genes in tobacco.